IMPLEMENTATION OF E-VOTING: INCREASING COMMUNITY PARTICIPATION FOR QUALITY ELECTIONS - Zainul Djumadin (Jurnal Ekonomi, 2022)
General elections are a pillar of democracy that determines the representation of the people in government. This research aims to explore the potential for implementing E-Voting as an innovative solution to increase public participation in general elections, with a focus on improving the quality of the election process. The research method involved literature analysis, interviews with information technology experts, and community surveys to gain a comprehensive understanding of the potential and barriers to implementing E-Voting. The research results show that the implementation of Electronic Voting (E-Voting) has a positive impact in increasing voter participation, efficiency and transparency in general elections. E-Voting overcomes traditional barriers such as long queues and time constraints by providing easier access and a more flexible voting experience. However, challenges such as system security, legal compliance, and technology engagement across all levels of society need to be addressed to ensure successful implementation. In conclusion, E-Voting has great potential to be an effective tool in realizing more inclusive and modern general elections, as long as these challenges can be overcome with appropriate and measurable solutions.